Respostas
respondido por:
2
7x^2 + 28x + 21 = 0
a= 7; b= 28 e c= 21
Δ= b^2 - 4*a*c
Δ= 28^2 - 4*7*21
Δ=784 - 588
Δ = 196
x = (-b +-√Δ)/2a
x = (-28 +-√196)/2*7
x = (-28 +- 14)/ 14
x1 = (-28 + 14)/14
x1 = (-14)/14
x1 = -1
x2 = (-28 - 14)/14
x2 = (-42)/14
x2 = -3
a= 7; b= 28 e c= 21
Δ= b^2 - 4*a*c
Δ= 28^2 - 4*7*21
Δ=784 - 588
Δ = 196
x = (-b +-√Δ)/2a
x = (-28 +-√196)/2*7
x = (-28 +- 14)/ 14
x1 = (-28 + 14)/14
x1 = (-14)/14
x1 = -1
x2 = (-28 - 14)/14
x2 = (-42)/14
x2 = -3
AvillaLivia:
isso realmente ta certo??
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás